Evaluation of the Implementation of Community Policing in Darfur - خالد، عاطف عبدالعزيز (القيادة العامة لشرطة الشارقة - مركز بحوث الشرطة, 2015)
The research aims to evaluate UN Police's Community Policing performance at Darfur Province, Sudan, since it started up to 2014. The research started with identifying Community Policing and its core components: community partnerships, problem solving and organizational transformation. It also sheds light on the integration of community policing into a democratic policing environment and the security needs of the Internally Displaced Persons ( IDPs) across Darfur since the conflict began in 2003, leading to the implementation of community policing in Darfur which is based on the UN Security Council Resolution 1769 (2007), and Doha Document for Peace in Darfur. Research also throws spotlight on the implementation of community policing activities following Community Policing Network which consists of Community Safety Committee, Zone Safety Coordinators and Community Policing Volunteers. It also demonstrates the UNAMID role in community policing activities such as Training and Capacity – building Activities, Community Outreach and awareness activities. Research then evaluated UNAMID Police's implementation of Community Policing in Darfur by setting forth statistics and comparison matrix of some of community policing activities in a period of 2 years to show the progress of the implementation of these activities. A questionnaire was also administered to UNAMID's Police Teams in Darfur to explore difficulties and obstacles they face as well as their perceptions about ways of developing community policing activities. Recommendations of the research included re-operationalization of community policing activities.
يستهدف البحث تقييم الكيفية التي يتم بها استخدام الشرطة المجتمعية من قبل شرطة بعثة الأمم المتحدة في دارفور بالسودان في عملية المصالحة وبناء السلام والثقة، وخاصة داخل معسكرات النازحين بإقليم دارفور، وذلك منذ بدء العمل باتفاقية الدوحة وحتى عام 2014. وقد بدأ البحث بالتعريف بمنظومة الشرطة المجتمعية ومكوناتها الرئيسية الثلاثة وهى المشاركة المجتمعية، وحل المشكلات، والتحول التنظيمي، وكذا توضيح ماهية الشرطة المجتمعية كفلسفة عمل للمنظمة الشرطية للتحول بها نحو الشرطة الديموقراطية، ثم تناول البحث استعراض الوضع الإنساني عقب اشتعال النزاع في 2003، وما تطلب ذلك من تفعيل الشرطة المجتمعية في الإقليم، والتي ارتكزت على قرار مجلس الأمن الدولي رقم 1769 / 2007 ومقررات اتفاقية الدوحة للسلام في دارفور من اجل خلق آليه لبناء الثقة وحل المشكلات المحلية، وأستعرض البحث اطار العمل التطبيقي للشرطة المجتمعية في دارفور والذى يقوم على إنشاء لجان امن مجتمعي، وتعيين منسقي أمن للمناطق وتدريب متطوعين من أهالي المعسكرات على الشرطة المجتمعية، ودور بعثة الأمم المتحدة في التدريب على أنشطة بناء الثقة، وأنشطة التوعية، عقب ذلك بدء الباحث في عمل تقييم لهذه الأنشطة حيث عرض لإحصائيات حول الأنشطة التي تطبقها شرطة الأمم المتحدة في مجال الشرطة المجتمعية، ومقارنة لمستويات تنفيذها خلال عامين، ثم انتقل البحث إلي عمل استبيان شمل ضباط الأمم المتحدة للشرطة المجتمعية العاملين في عدد 30 محطة لشرطة الأمم المتحدة على مستوى كافة قطاعات دارفور الخمسة، حيث تم تقسيم الاستبيان إلى قسمين، الأول حول التحديات العامة اشتمل على العقبات والتحديات المرتبطة بالعمليات على الأرض والصعوبات والتحديات الخارجية التي تعيق عمل الشرطة المجتمعية أما القسم الثاني فاستعرض رؤية العاملين في مجال الشرطة المجتمعية حول تطوير الأداء وتطوير العلاقة مع الشرطة المحلية ومع النازحين. وخلص البحث إلى نتائج تمثلت في وجود فجوة كبيرة بين المأمول والمتاح وقدم مقترحات لتطوير عمل الشرطة المجتمعية في دارفور لتلافى المشكلات التي أظهرها الاستبيان.
Keywords: الشرطة -- الشرطة المجتمعية -- تقييم الاداء -- دارفور